The Beginning of the Human Rights 5th Generation: A Lesson from Covid-19 Outbreak in Indonesia - Al-Fatih, Sholahuddin; Aditya, Zaka Firma (Faculty of Law, Jambi University, 2024)
This research tries to find the root cause of the spread of fake news during the Covid-19 pandemic in Indonesia. The Indonesian Ministry of Information and Communication recorded that there were 519 or 56% of the total 926 fake news during semester 1 of 2020. This figure doubled in October 2020 with a total of 1,028 fake news in the health sector especially dealing with Covid-19. Whereas, in the perspective of Human Rights, everyone has the right to get the correct information. This statement is guaranteed in Article 28F of the 1945 Constitution, Article 19 UDHR, and Article 19 of the ICCPR. These problems were then analyzed using a prescriptive method to find new concepts related to fake news to prevent a pandemic. This study indicates that the spread of fake news during the Covid-19 pandemic in Indonesia was greatly influenced by low literacy and public knowledge, lack of self-awareness, and a tendency to attack political opponents